The Influence of Digital Competence on Lecturer Performance: The Mediation Role of Psychological Empowerment on Lecturers In The Management Study Program - Mirza Mirza (CV Putra Publisher, 2026)
This study aims to analyze the effect of digital competence on lecturer performance with psychological empowerment as a mediating variable in lecturers of the Management Study Program. The research approach uses a quantitative method with Structural Equation Modeling analysis based on Partial Least Square (SEM-PLS). Data were collected through questionnaires and analyzed using validity and reliability tests, as well as structural model testing. The results of the study indicate that digital competence has a positive and significant effect on lecturer performance. In addition, digital competence also has a positive effect on psychological empowerment, and psychological empowerment has a positive effect on lecturer performance. The results of the mediation test indicate that psychological empowerment is able to partially mediate the relationship between digital competence and lecturer performance. This finding indicates that improving lecturer performance is not only determined by technical abilities in mastering digital technology, but also by psychological conditions in the form of psychological empowerment that strengthens the implementation of these competencies. Thus, developing lecturer performance in the digital era needs to integrate improving digital competence and strengthening psychological aspects simultaneously